Uma Ferramenta de Gamificação para Avaliação de Aprendizagem de Disciplinas de Graduação em Computação. - OLIVEIRA, Renato de Araújo (2018)
Academic life is a period when students invest time and effort. However the lack of student motivation is an issue that concerns teachers. Recent research has shown that Gamification has the property of inducing one’s behavior, improving their engagement in a given task. Therefore, teachers have employed Gamification in classrooms as a motivating strategy. This dissertation specifies and implements a gamification tool to be applied to the learning assessment of Computer Science undergraduate courses. The developed tool has been applied in two courses at Universidade Federal do Maranhão, namely Algorithms I and Computing Foundations. Students’ profiles have been analyzed and their behaviors mapped according to their utilization of the technologies involved. Our results demonstrate that the tool’s application improved student’s engagement in task resolution, achieving 85% of completed tasks and 38% of tasks returned within the deadline set by the teacher.